Performance analysis and Scout efficiency in a professional soccer team in the year 2022 (Research, Society and Development, 2023)
The present study aimed to analyze the efficiency of the scout method in a professional soccer team. This is an applied, descriptive research with a quantitative and field approach. The sample consisted of 23 professional male soccer players during the pre-season period and the championship of the second division of Paraná soccer in the year 2022. For data collection, a table was used to record wrong passes, finalizations, loss of the ball, tackles, fouls committed and suffered, impediments and corner kicks. Data were collected during the 13 games of the season, four training games and nine official games. The data treatment considered the first seven games as the beginning, where the scout analysis was in the phase in which adjustments were made in the tactics and technique of the players. The other games were considered the final phase of the season (high performance). It was possible to conclude that despite obtaining some insignificant numbers in the collective aspect, the individual aspect obtained considerable improvement, making it possible to point out the scout as an indispensable tool in a soccer club today.